A saline contrast‐enhanced echocardiography‐guided approach to cryoballoon ablation. Issue 7 (11th June 2020) - Kanda, Takashi; Masuda, Masaharu; Kurata, Naoya; Asai, Mitsutoshi; Iida, Osamu; Okamoto, Shin; Ishihara, Takayuki; Nanto, Kiyonori; Tsujimura, Takuya; Okuno, Shota; Matsuda, Yasuhiro; Hata, Yosuke; et al.
Abstract: Background: Pulmonary vein isolation (PVI) with a cryoballoon usually uses iodinated contrast medium for confirmation of venous occlusion. We hypothesized that an alternative to angiography with iodinated contrast, saline bolus‐enhanced echocardiography with the microbubbles formed in situ, could be used to assess venous occlusion. We sought to assess the efficacy and safety of the contrast‐enhanced intracardiac echocardiographic (ICE) approach. Methods: Thirty‐four consecutive patients without iodine sensitivity or renal insufficiency were studied to assess the accuracy of ICE‐guided PV occlusion underwent both angiographic guidance and ICE guidance (validation group). Twenty consecutive patients with paroxysmal atrial fibrillation (AF) and contraindications to iodinated contrast medium (ICE‐guided group) underwent PV occlusion and ablation with ICE guidance alone. Procedural results and clinical outcomes were compared with those of 245 control patients undergoing PVI by the conventional angiographic method (control group). Results: In the validation group, ICE‐guided PV occlusion was as effective as angiography‐guided PV occlusion. In the ICE‐guided group, two patients required touch‐up ablation using a radiofrequency ablation catheter with fluoroscopic guidance. Procedure time, radiation exposure, and requirements for touch‐up ablation were similar between the ICE‐guided group and the control group. In patients requiring only PVI, the ICE‐guided approach involved significantly less radiation exposure than the conventional approach. There was no significant difference in atrial fibrillation (AF)‐free survival rate between the two groups during a follow‐up period of 14 ± 6 months. Conclusions: An echo‐guided approach using saline infusion was effective in terms of avoidance of iodinated contrast use and radiation exposure.